Location Choice of Distribution Center for Freshfood E-Commerce by the Approaching of Spatial Center of Gravity Method and Implementation of Halal Logistics Standard MS2400 (Case Study of Fresh Food Delivery to JABODETABEK) - Muhammad Lutfi Siregar Siregar; Afuan Zahradika (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The purpose of this research is trying to solve problems by various logistics parties in delivering fresh food (freshfood e-commerce) such as the high of shipping costs and the difficulty of maintaining the quality of fresh products because the value of these products will decrease exponentially after harvest. Implementation for strategy of grouping goods at distribution center in an optimal location as a transit center will result the reduction costs in the shipping process. The Center of Gravity (CoG) method is applied to measure the optimal point of the distribution location but this model does not consider regional spatial effects such as the effects of congestion, natural disasters, topography, economy, and security, therefore a spatial approach was added in the application of the Center of Gravity method (CoG) to reduce the spatial effects. The application of MS2400 as one of the best halal logistics standards is also applied to make standard procedures and layout designs to prevent decreasing in the quality of the products. The results of implementation the CoG method by using spatial approach found several recommendations for latitude and longitude points for distribution locations based on 5 delivery zones, such as Zone DC 1 Tangerang (-6.28010, 106.6684), Zone DC 2 Jakarta (6.16544, 106.7465), Zone DC 3 Jakarta (-6.276778, 106.8042), Zone DC 4 Bogor (-6.503629, 106.8340), and Zone DC 5 Bekasi (-6.27263, 107.19930). However, it was found that the usage of the CoG method with a spatial approach was not so significant in reducing spatial problems when it was compared to the classical CoG model. The implementation of the MS2400 standard requires several additional facilities such as temperature determination, a special medical checkup room, a prayer room, a cleaning facility room, a hygienic toilet room, a vehicle break room, and a room for separating damaged products.